(untitled) (Journal of the College of Basic Education, 2024)
The aim of my current research is (to identify the extent of the use of electronic learning platforms in the College of Education (Department of History) from the point of view of professors and also to identify the attitudes of professors towards them) and to achieve these goals, the researcher followed the descriptive approach to the research, and chose the research sample, which amounted to (78) professors from the Department of History, Faculty of Education. Then the researcher prepared a questionnaire for the extent of the use of e-learning platforms from the point of view of professors of the Department of History at the College of Education, consisting of (30) items to know the extent of the use of e-learning platforms, and also prepared a measure to know the attitudes of professors towards e-learning platforms, the researcher made sure of their sincerity by presenting them to a number of arbitrators an 1- The general level of use of the professors of the Department of History of electronic learning platforms in the teaching process and giving lectures is rather weak, due to the difficulties and obstacles they face during its use during the quarantine period and the spread of the Corona virus, in addition to their lack of experience in the electronic field and electronic technologies affected the degree of their use of them in the teaching process. 2- Professors of the Department of History have positive attitudes towards e-learning platforms. Recommendations 1- Placing professors in the Department of History under rehabilitation and training programs on modern and advanced electronic educational platforms in order to keep pace with the development in the electronic and technical field and benefit from it in the future in the field of teaching, giving electronic lectures, facing any emergency, and keeping pace with modern teaching methods and methods that rely heavily on technology. 2- Developing and supporting the Internet media in educational institutions, especially universities, in order to facilitate the use of electronic learning platforms. propositions To complement the aspects of the current research, the researcher proposes the following 1- Conducting a similar study on students and professors in other departments in the College of Education and the university in general and comparing it with the results of the current research. 1- Preparing an electronic training program to develop professors and students on the technology of e-learning platformsd experts in teaching methods, and then also verified the stability of the questionnaire by re-testing a sample consisting of (20) professors after two weeks of the application of the test, as it reached ( 0.86) which is a good stability coefficient